(Electronics and Photonics Division Award Address) Compound Semiconductor Science and Technology: A Retrospective. (25th April 2017) - Buckley, D. Noel
Abstract : From the earliest days, there has been interest in GaAs and other compound semiconductors due to higher electron mobility than silicon and suitability for optical applications. It was shown in 1962 that semiconductors such as silicon are not suitable for lasers and compound semiconductors were suggested. In the fall of 1962, several groups demonstrated semiconductor lasers under pulsed conditions at 77 K and double heterostructure (DH) laser diodes were achieved in 1970. Coinciding with major advances in fiber optics technology, this provided an enormous impetus for the development of compound semiconductor technology. Epitaxial crystal growth is a most important part of the technology. Liquid phase epitaxy was initially used but was replaced by vapor-phase and molecular beam epitaxy. MOCVD eventually became the vapor-phase technique of choice. Following a breakthrough in GaN technology in the 1990s, the impact of GaN technology is enormous and GaN-based LEDs are rapidly becoming the lighting technology of choice.